2015
DOI: 10.1039/c5dt01193k
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle decorated graphene sheet-polypyrrole based nanocomposite: its synthesis, characterization and genosensing application

Abstract: We report herein the synthesis of gold nanoparticle (GNP) decorated-graphene sheets (GO-GNPs) using the template of graphene oxide (GO) by a one-pot solution-based method. A polypyrrole-GO decorated GNP nanocomposite (GO-GNP/PPY) has been electropolymerized using a potentiodynamic method on an indium tin oxide (ITO) coated glass substrate. The as-synthesized nanocomposites are characterized by transmission electron microscopy, energy dispersive X-ray spectroscopy, scanning electron microscopy, thermogravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Furthermore for all of the cys-N-rGOs studied, the appearance of a new peak near 1435 cm –1 (enlarged Figure A), which can be attributed to C–S vibrations, was also detected . A detailed inspection of the two peaks positioned at 1384 and 1548 cm –1 (enlarged Figure A), which can be attributed to the stretching vibrations of C–N and N–H, respectively, was also identified. It is essential to note that all the peaks corresponding to N–H, C–N, and S–H vibrations were not detected in the FTIR spectra of their respective N-rGO precursors. Moreover, no absorption associated with the stretching vibration of the S–H group, commonly recorded between 2500 and 2600 cm –1 was observed, signifying the breaking of the S–H bond in cysteamine to covalently attach on the reduced graphene sheets via thiol-ene click functionalization. , Coupled with the strong evidence from these observations, we can infer the successful grafting of the cysteamine functional groups onto the graphene framework via the thermal thiol-ene click reaction, which converted the N-GO and N-rGO precursors to cys-N-GO and cys-N-rGOs, respectively.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore for all of the cys-N-rGOs studied, the appearance of a new peak near 1435 cm –1 (enlarged Figure A), which can be attributed to C–S vibrations, was also detected . A detailed inspection of the two peaks positioned at 1384 and 1548 cm –1 (enlarged Figure A), which can be attributed to the stretching vibrations of C–N and N–H, respectively, was also identified. It is essential to note that all the peaks corresponding to N–H, C–N, and S–H vibrations were not detected in the FTIR spectra of their respective N-rGO precursors. Moreover, no absorption associated with the stretching vibration of the S–H group, commonly recorded between 2500 and 2600 cm –1 was observed, signifying the breaking of the S–H bond in cysteamine to covalently attach on the reduced graphene sheets via thiol-ene click functionalization. , Coupled with the strong evidence from these observations, we can infer the successful grafting of the cysteamine functional groups onto the graphene framework via the thermal thiol-ene click reaction, which converted the N-GO and N-rGO precursors to cys-N-GO and cys-N-rGOs, respectively.…”
Section: Resultsmentioning
confidence: 81%
“…55 A detailed inspection of the two peaks positioned at 1384 and 1548 cm –1 (enlarged Figure 7A), which can be attributed to the stretching vibrations of C–N and N–H, respectively, was also identified. 5658 It is essential to note that all the peaks corresponding to N–H, C–N, and S–H vibrations were not detected in the FTIR spectra of their respective N-rGO precursors. Moreover, no absorption associated with the stretching vibration of the S–H group, commonly recorded between 2500 and 2600 cm –1 was observed, signifying the breaking of the S–H bond in cysteamine to covalently attach on the reduced graphene sheets via thiol-ene click functionalization.…”
Section: Resultsmentioning
confidence: 99%
“…Lam et al reported a dopamine electrochemical biosensor based on the electrodeposition of PPy and nanoAu on chemical etching-graphene modified electrode [13]. More recently, Tiwari et al reported a chemical-electrochemical route for the synthesis of a PPy, graphene oxide, and nanoAu nanocomposite [14]. First, a nanoAu–graphene sheet was fabricated using a chemical method, with two reduction agents sodium citrate dehydrate and sodium borohydrate at 100 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The final product was fabricated via the attachment of a DNA probe on the surface of the nanocomposite electrode. The incorporation of polypyrrole into this genosensor improved the conductivity of the electrode and enhanced the immobilization of the DNA probe onto the electrode surface [232] .…”
Section: Gene Sensors and Immunological Sensorsmentioning
confidence: 99%